PERBANDINGAN DAYA DUKUNG TIANG PANCANG BERDASARKAN METODE ANALITIS DAN PILE DRIVING ANALYZER TEST JEMBATAN WAITUNSA - Lawalata, Alicya; Latar, Sjafrudin; Betaubun, Renny James (Journal Agregate, 2025)
Waitunsa Bridge is located in Siwalalat subdistrict, Eastern Seram Regency Siwalalat Seram Regency, Laimu Werinama Road Section with a Stretch Length of 300 M and a Width of 9 M. During the project implementation, the foundation work on the bridge was piling, where the planned piles that went into the ground were 1150 KN, but when tested using the Pile Driving Analyzer (PDA) Test, it had exceeded the planned limit, the piles that entered the ground were more than 3000 KN. The aim of this research is to analyze the bearing capacity value of a single pile foundation using analytical methods on the Wai Tunsa bridge, East Seram and to obtain a comparison of the calculation results using the analytical method and the results of the Pile Driving Analyzer test on the foundation of the Wai Tunsa bridge, Seram. East. In writing the methods used to analyze the bearing capacity of piles are the Meyerhoff method, Tomlinson method, as well as the reduction in pile foundations and well foundations is the Meyerhof method. The results of calculations carried out at 3 points, namely Abutment 1 (A1), Pier 1 (P1), and Abutment 2 (A2) on the Waitunsa Bridge work, Siwalalat subdistrict, East Seram Regency, from the results of manual analysis, it can be concluded that the Tomlinson method has good value. is closer than the Mayerhoff method to the PDA Test. Qu = 402.89 tons compared to 336 - 388 tons at A1, Qu = 384.74 tons compared to 373 – 389 tons at P1, and Qu = 397.57 tons compared to 347 – 389 tons.